Plasmacytoid Dendritic Cells Protect Against Middle Cerebral Artery Occlusion Induced Brain Injury by Priming Regulatory T Cells - Chen, Chen; Chencheng, Zhang; Cuiying, Liu; Xiaokun, Geng (Frontiers in Cellular Neuroscience, 2020)
Regulatory T cells (Tregs) play an anti-inflammatory effect to protect against ischemic stroke. Plasmacytoid dendritic cells (pDCs) can induce regulatory T cells tolerance in sterile-inflammation conditions. However, whether and how pDCs-mediated Tregs response play a part in the pathology of ischemic stroke remains unclear. In this study, we showed that pDCs were increased in brain of middle cerebral artery occlusion (MCAO) mice. Depletion of pDCs with 120G8 exacerbated MCAO-induced brain injury, peripheral pro-inflammation response and decreased the systemic Tregs in mice. Furthermore, the data of mixed lymphocyte reaction (MLR) in vitro demonstrate that splenic pDCs from MCAO mice can significantly promote Tregs proliferation, accompanying with the increased expression of indoleamine 2,3-dioxygenase 1 (IDO1) on pDCs. Taken together, the findings here suggested that under the pathologic state of stroke, pDCs protect against MCAO-induced brain injury by priming Tregs, illustrating that pDCs represented as a therapeutic target for the prevention of ischemic brain injury.